Distribution of saxitoxin producing algae in Jakarta Bay and the implication to saxitoxin concentration in green mussel. Issue 1 (January 2022) - Dwiyitno, D; Barokah, G R; Rustiani, R K; Wibowo, S
Abstract: Harmful algae blooms (HABs) have been associated with an annual incidence in Jakarta Bay. The The present study aimed to investigate the concentration of dinoflagellates producing saxitoxins (STXs) in Cilincing and Kalibaru regions and the STXs concentration in mussel species from this coastal water. A sampling of phytoplankton, green mussel ( Perna viridis ), and environmental parameters were measured during the transition from wet to dry season. The water nutrients of the Cilincing region, mainly nitrite and ammonia in some green mussel aquaculture, have exceeded the recommended concentration to support the eutrophication/algae bloom. The N/P ratio at the study area was between 10 and 22. Plankton identification found STXs producing dinoflagellates, i.e., Alexandrium sp. and Gymnodinium sp. Other species of dinoflagellates and diatom showed predominantly to trigger algae Bloom, such as Skeletonema sp., Chaetoceros sp., Prorocentrum sp., Gonyaulax sp., Protoperidinium sp., and Nitzchia sp. Further analysis of saxitoxin in mussel samples from Cilincing and Kalibar showed STX concentrations of 10.15 μg/100 g and 21.24 μg/100 g, respectively, which is fairly below the official maximum limit (80 μg/100 g) as set by FAO/WHO or national standard.